2009
DOI: 10.1111/j.1440-1819.2009.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a Japanese version of the Cambridge depersonalization scale as a screening instrument for depersonalization disorder

Abstract: Aims:The Cambridge Depersonalization Scale (CDS) is an instrument that has obtained reliability and validity in some countries for use in detecting depersonalization disorder under clinical conditions, but not yet in Japan under non-psychiatric conditions. The purposes of this study were to develop a Japanese version of the CDS (J-CDS) and to examine its reliability and validity as an instrument for screening depersonalization disorder under non-clinical conditions. Methods: The CDS was translated from English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Soma-se a isso o tema de natureza pessoal e íntima abordado nesta pesquisa. Embora a tradução para o português do questionário que utilizamos neste estudo (CDS-BR) ainda careça de uma análise formal de validação transcultural para assegurar sua estabilidade, a Cambridge Depersonalization Scale é uma ferramenta testada e validada transculturalmente em diversos países (CDS, CDS-J, CDS-IV, CDS9, CDS-VE) 9 , mantendo sua acurácia e confiabilidade em diversos países onde foi testada 7,10,14,15 . Entretanto, recomenda-se cautela na interpretação destes resultados.…”
Section: Resultsunclassified
“…Soma-se a isso o tema de natureza pessoal e íntima abordado nesta pesquisa. Embora a tradução para o português do questionário que utilizamos neste estudo (CDS-BR) ainda careça de uma análise formal de validação transcultural para assegurar sua estabilidade, a Cambridge Depersonalization Scale é uma ferramenta testada e validada transculturalmente em diversos países (CDS, CDS-J, CDS-IV, CDS9, CDS-VE) 9 , mantendo sua acurácia e confiabilidade em diversos países onde foi testada 7,10,14,15 . Entretanto, recomenda-se cautela na interpretação destes resultados.…”
Section: Resultsunclassified
“…Validated CDS versions translated into German, Spanish and Japanese (Michal et al 2004; Molina Castillo et al 2006; Sugiura et al 2009) showed high internal consistency (Cronbach's alpha: 0.95, 0.94 and 0.94, respectively) and high correlations with DES DP/DR subscale (Spearman coefficient: 0.75, 0.60 and 0.65, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Sugiura et al . showed the reliability and validity of the Japanese version of the Cambridge Depersonalization Scale (J‐CDS) and set its best cut‐off at 60, based on 59 participants (12 patients with depersonalization disorder, 11 individuals having recovered from depersonalization and 36 healthy controls) 2 . Nishi et al .…”
Section: One Of Our Missionsmentioning
confidence: 99%
“…1 Sugiura et al showed the reliability and validity of the Japanese version of the Cambridge Depersonalization Scale (J-CDS) and set its best cut-off at 60, based on 59 participants (12 patients with depersonalization disorder, 11 individuals having recovered from depersonalization and 36 healthy controls). 2 Nishi et al reported that the score on the Japanese version of the Peritraumatic Distress Inventory (PDI) predicted subsequent post-traumatic stress disorder in survivors of severe motor vehicle accidents with sensitivity (77%) and specificity (82%) at a cutoff of 23. 3 Koyama et al reported the utility of the Japanese version of the Checklist for Autism in Toddlers (CHAT-J) for predicting pervasive developmental disorders (PDD) based on 52 two-year-old children with PDD and 48 two-year-old children without PDD.…”
mentioning
confidence: 99%